A reconfigurable soft wall-climbing robot actuated by electromagnet. (24th March 2021) - Zhang, Wendong; Zhang, Wen; Sun, Zhenguo
This article demonstrates a reconfigurable soft wall-climbing robot actuated by electromagnet. The robot follows the earthworm movement gait and is capable of translation, deflection, and rotation movement while working on a sloping ferromagnetic wall. Also the electromagnetic actuator provides a significant improvement in expeditiousness compared with existing actuation modes. The speed of the robot can be adjusted by modulating the power frequency. When the period of motion cycle is 30 ms, the speed is about 26.5 mm s −1, and the robot can rotate with a velocity of 14.1° s −1 on the horizontal plane. It can also climb a vertical wall at the speed of 12.6 mm s −1 . The robot is composed of two kinds of modules which can be connected by the magnets embedded. It can also be reconfigured in different working conditions, such as crossing an inaccessible gap, and thus has the potential to be used in flaw detection, surface cleaning, and exploration of ferromagnetic structures.